The Impacts of CGIAR Research: A Review of Recent Evidence - Renkow, M.; Byerlee, D. (Elsevier, 2010)
We review evidence on the impacts of CGIAR research published since 2000 in order to provide insights into how successful the CGIAR Centers have been in pursuing the System’s core missions. Our review suggests that the CGIAR research contributions in crop genetic improvement, pest management, natural resources management, and policy research have, in the aggregate, yielded strongly positive impacts relative to investment, and appear likely to continue doing so.